Integrating Digital Citizenship in Character Education through Interpersonal Communication - Tsamar Nur Aini; Muhammad Sahlan; Mohammad Zainul Arifin Billa (JUMPA : Jurnal Manajemen Pendidikan, 2023)
This study focuses on the role of interpersonal communication, mainly through the Peer Mentorship program, in developing students’ character in madrasahs. The main objective of this study is to explore and evaluate the effectiveness of Peer Mentorship in shaping students’ moral, social, and spiritual character. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and document analysis and analyzed using Miles and Huberman analysis. The results of the study indicate that interpersonal communication facilitated by Peer Mentorship significantly improves students’ leadership, responsibility, and self-confidence. In addition, this program also helps students internalize moral and ethical values relevant to contemporary social challenges such as cultural diversity and digital ethics. The implications of this study emphasize the importance of the interpersonal communication approach in character education, which other madrasahs in Indonesia can adopt to improve the overall quality of character education.